1990
DOI: 10.1002/pola.1990.080280718
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyamine resins from epoxy resins

Abstract: Polyamine resins were synthesized by the preparation of ketimine‐terminated resins from epoxy resin and ketimine blocked diethylene triamine (1) and subsequent hydrolysis. 1 was prepared by the condensation reaction of diethylene triamine with methyl isobutyl ketone catalyzed by acid. The hydrolysis of ketimine containing resin was evaluated by the change of the pH value of reaction mixture and the infrared spectroscopy and gel permeation chromatography curve of the resulting product. The hydrolytic rate of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Under an identical stirring rate, the reaction of SMA with POE2000 diamine in toluene (25 wt %) produced a gel within 50 s, but in MEK as the solvent it took 315 s (Table I). A systematic study indicated that gel formation was much slower in a ketone solvent such as MEK than in toluene, perhaps because of the formation of an equilibrium imine14, 15 intermediate (CN) between the POE2000 amine and the ketone solvent. By adjusting the amount of MEK solvent, the gel time could be prolonged from 50 to 710 s. This finding allows us to develop a convenient method for preparing polymer films.…”
Section: Resultsmentioning
confidence: 99%
“…Under an identical stirring rate, the reaction of SMA with POE2000 diamine in toluene (25 wt %) produced a gel within 50 s, but in MEK as the solvent it took 315 s (Table I). A systematic study indicated that gel formation was much slower in a ketone solvent such as MEK than in toluene, perhaps because of the formation of an equilibrium imine14, 15 intermediate (CN) between the POE2000 amine and the ketone solvent. By adjusting the amount of MEK solvent, the gel time could be prolonged from 50 to 710 s. This finding allows us to develop a convenient method for preparing polymer films.…”
Section: Resultsmentioning
confidence: 99%
“…Epoxy resins are frequently cured by amines; however, the curing process is sometimes incomplete mainly because of insufficient mixing of curable and catalytic pastes. This problem may be solved by development of a one‐component epoxy resin containing a latent hardener such as an imine 2, 3. The curing system of imine‐based one‐component epoxy resin is composed of two steps, that is, the first step is the hydrolysis of the imines releasing amines, and the second step is the reaction of the generated amine with epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…This problem may be solved by development of a one-component epoxy resin containing a latent hardener such as an imine. 2,3 The curing system of imine-based onecomponent epoxy resin is composed of two steps, that is, the first step is the hydrolysis of the imines releasing amines, and the second step is the reaction of the generated amine with epox-ides. We have recently reported that diethyl ketone-based imines show a faster hydrolysis rate than industrially used methyl ethyl ketone-and methyl isobutyl ketone-based imines, and onecomponent epoxy resins with diethyl ketonebased imines show good curing properties and storage stability.…”
Section: Introductionmentioning
confidence: 99%